Private law, nudging and behavioural economic analysis : the mandated-choice model - Karampatzos, Antonis (Routledge, 2020)
"Offering a fresh perspective on "nudging", this book uses legal paternalism to explore how legal systems may promote good policies without ignoring personal autonomy. It suggests that the dilemma between inefficient opt-in rules and autonomy restricting opt-out schemes fails to realistically capture the span of options available to the policy maker. There is a third path, namely the 'mandated-choice model'. The book is dedicated to presenting this model and exploring its great potential. Contract law, consumer protection, products safety and regulatory problems such as organ donation or excessive borrowing are the setting for the discussion. Familiarising the reader with a hot debate on paternalism, behavioural economics and private law, this book takes a further step and links this behavioural law and economics discussion with philosophical considerations to shed a light on modern challenges, such as organ donation or consumers protection, by adopting an openly interdisciplinary approach. The book will be of interest to students and scholars of contract law, legal systems, behavioural law and economics, and consumer law"-- Provided by publisher
Keywords: Law and economics -- Psychological aspects.; Civil law -- Economic aspects.; Public policy (Law) -- Psychological aspects.; Droit et économie politique -- Aspect psychologique.; Ordre public -- Aspect psychologique.; LAW -- General.; Civil law -- Economic aspects; Nudge theory